Detrital zircons from Lower Triassic sandstones, Belsky depression, Pre-Uralian foredeep: LA-ICP-MS U-Pb isotopic ages and distribution of rare and trace elements - A. V. Maslov; G. A. Mizens; G. M. Vovna; V. I. Kiselev; Yu. L. Ronkin (Литосфера, 2016)
Lower Triassic sandstones in the southern part of Belsky depression (Pre-Uralian foredeep) contain detrital zircons with concordant U-Pb isotopic ages ranging from Neoarchean to the boundary of the Carboniferous and Permian. The distribution of rare and trace elements in zircons suggests that the majority of them fall into the Triassic sandstones due to erosion of basic rocks (or, taking into account the possibility of multiple recycling, most of them are crystallized in the rocks of basic composition). These data indicate a much wider age range of rocks in provenances in the Early Triassic, than it follows from petrographic observations. The micropetrografic data testify that the magmatic complexes which are distributed at present in Sakmara area were the sources of zircons with the Early and Middle Paleozoic datings. Detrital zircons with the Proterozoic and Neoarchean ages are likely redeposited from Riphean-Vendian Ural-Tau zone, where they were brought due to erosion of East European platform base. A small proportion of crystals with Late Paleozoic ages taking into account the geochemical and petrographic data, permits suggest that granite massifs of the Main Granitic axis of the Urals, during the formation of Pre-Uralian molasses has not been involved into erosion. Perhaps they have not yet been withdrawn to the surface, or were placed to the East line of the watershed. At the same time, a significant number of zircons with Precambrian age indicates that the Ural-Tau metamorphic formations were in the erosion zone. Consequently, the orogen watershed at that time was to the east of the zone. This is also evidenced by the presence in the Lower Triassic sandstones few crystals of zircon with Carboniferous age, the source of which could be to the west of modern Magnitogorsk megazone. On the basis of these data we suggest that the forming of coarse clastic formations of the final stage of orogeny in the southern Urals occurred mainly due to erosion of sedimentary, igneous and metamorphic complexes from modern western slope of the axial zone of the Urals.